Case report: Severe arrhythmogenic cardiomyopathy in a young girl with compound heterozygous DSG2 and MYBPC3 variants with a 6-year follow-up - Hashizume, Ryotaro; Imai, Hiroshi; Ohashi, Hiroyuki; Sawada, Hirofumi; Yodoya, Noriko; Okamoto, Ryuji; Dohi, Kaoru; Kasai, Chika; Kitajima, Takahito; Fujiwara, Takumi; Mochiki, Ikuyo; Nakatani, Kaname; et al. (Frontiers in Genetics, 2025)
IntroductionArrhythmogenic cardiomyopathy (ACM) is an inherited cardiac disorder characterized by progressive fibrofatty replacement of the myocardium. In the Japanese population, variants of the desmoglein-2 (DSG2) gene are a major cause of ACM, typically following an autosomal recessive inheritance pattern. Myosin-binding protein C (MYBPC3) variants are primarily associated with hypertrophic cardiomyopathy (HCM). Here, we report a severe pediatric case of ACM associated with compound heterozygous DSG2 and MYBPC3 variants.Case PresentationA 6-year-old asymptomatic girl was diagnosed with ACM based on abnormal electrocardiogram findings, including epsilon waves, and T-wave inversions in leads V1-6 and III. Echocardiography revealed right ventricular (RV) dilatation (RV outflow tract diameter/body surface area: 22.9 mm/m2) and reduced RV function (fractional area change: 18.0%). Cardiac magnetic resonance imaging confirmed RV dysfunction (ejection fraction [EF]: 9.7%) and left ventricular (LV) involvement (EF: 48.9%). Genetic testing identified compound heterozygous DSG2 variants (p.Arg119* and p. Arg292Cys) and an MYBPC3 variant (p.Arg820Gln). The patient remained asymptomatic until age 10.5 years, when she developed heart failure requiring hospitalization. Imaging revealed severe biventricular dilatation (LV end-diastolic volume index: 149.5 mL/m2; RV end-diastolic volume index: 255.9 mL/m2) and biventricular dysfunction (LVEF: 9.5%; RVEF: 9.7%). Despite medical management, the patient’s condition progressively worsened, and she was deemed eligible for heart transplantation.DiscussionThis case illustrates the potential for severe pediatric ACM associated with compound heterozygous DSG2 variants and a MYBPC3 variant. The DSG2 variants likely played a primary role disease pathogenesis, while the MYBPC3 variant may have exacerbated the phenotype. The coexistence of desmosomal and sarcomeric gene variants is rare in cardiomyopathies, making genotype-phenotype correlations complex. Further research is needed to elucidate the interplay between these genetic factors.ConclusionThis case underscores the genetic heterogeneity and phenotypic variability in inherited cardiomyopathies. It emphasizes the importance of comprehensive genetic testing and close monitoring of affected individuals and their families.